Neuroendocrıne Small Cell Carcinoma of the Endometrium: A Case Presentation - Hüseyin Görkemli; Kazım Gezginç; Fatma Yazıcı; Utku Dalkılıç; Salim Güngör (Medical Network, 2011)
To present a case of neuroendocrine differentiated small cell carcinoma of the endometrium with postmenopausal bleeding and its clinical, histological and immunohistochemical features are discussed. A 54-year-old woman (gravida 4, para 1), admitted to our clinic with a chief complaint of postmenopausal bleeding for 1 months. She has been in menopause for 10 years. On pelvic examination, she had 3 months-sized, firm, large, hard, and anteverted uterus. Cervicovaginal smear was normal. A subsequent endometrial curettage was suspicious for carcinoma. The patient underwent total abdominal hysterectomy with bilateral salpingooophorectomy and pelvic lymphadenectomy. Malignancy was confirmed from frozen section. The final pathology report confirmed neuroendocrine differentiated small cell carcinoma of the endometrium. The postoperative course was uneventful and the patient received chemotherapy including cisplatin and etoposide. These tumors have a propensity for systemic spread and poor prognosis; therefore, the stage of the tumor is an important prognostic factor. Early detection provides the only opportunity for long-term survival in patients with small cell carcinoma of endometrium.